A Model for Cloud Computing for Emergency Operation - Bedse, Shital Bedse; Ahire, Pratiksha; Dhondge, Prerna; Kunde, Harshali; Bhagwat, Sarika (International Journal of Computer Sciences and Engineering, 2020)
Cloud computing enables on demand network access to a share pool of configurable computing resources such as servers, storage and application. Cloud storage used to deliver the storage resources to the user over the Internet. Private cloud storage is restricted to a specific organization and data security risks are high in cloud storage. Hence, private cloud storage is built by utilizing the commodity machines within the organization and the important data is stored in it. When the utilization of such private cloud storage increases there will be an increase in the connection problem, performance, storage demand, privacy, security and data integrity. For connection problem we will implement offline data store and sync mechanism. Increase in storage demand leads to the enlargement of the cloud storage with additional storage nodes. During such enlargement, storage nodes in the cloud storage need to be balanced in terms of load. The key idea behind this is to develop a dynamic load balancing algorithm based on de-duplication to balance the load across the storage nodes during the expansion of private cloud storage. For maintaining privacy, security and data integrity we will use AES algorithm and SHA algorithm.